Development of Articulate Storyline Interactive Learning Media to Improve Light Vehicle Engine Knowledge - Sunarto, Sunarto; Anis, Samsudin; Widjanarko, Dwi (Universitas Negeri Semarang, 2025)
The learning problem of SMK N 1 Petarukan students of light vehicle engineering is the low achievement in understanding light vehicle engine materials. This research aims to develop, analyse the feasibility, practicality and effectiveness of Articulate Storyline learning media in improving students' engineering knowledge. This research uses the ADDIE development model (Analysis, Design,Development, Implementation, and Evaluation). The assessment of the feasibility of the media was carried out by three experts in the material and media, the practicality of the media in the value of 12 educators in this study72 students of class XI TKR SMKN 1 Petarukan. The results of the study show that the media that learning Articulate Storyline was declared feasible and practical. Statistical analysis showed a significant improvement after treatment. From the results of the N-gain test, the experimental class achieved an increase of 56.64% (medium category) compared to the control class of only 20.08% (low category). This shows an increase in student knowledge using the developed learning media. The Articulate Storyline interactive learning media has proven feasible and effective in improving the engineering knowledge of SMK students in light vehicle engineering.